SEANZA Lectures : eighth Seanza central banking course 5 Oct.- 11 Dec. 1970, Manila, Philippines - Central Bank of the Philippines ([Manila] : Bangko Sentral ng Pilipinas (Central Bank of Philippines), 1971)
This is a compilation in book form of the lectures delivered by specialists from universities and central banks of different countries and from international agencies such as the IBRD, IMF, and United Nations, at the 8th SEANZA Central Banking Course held from October 5 to December 11, 1970, in Manila, Republic of the Philippines.
rpm 10/05/2018
Loans
Keywords: Banks and banking; Financial institutions; Economic development; Manila, Philippines